Estar vivo é ser afetado : cozinheiros, ingredientes e afetos em uma cozinha imigrante - Altoé, Isabella Machado (2019)
The history of the world is a story of migrations: the continuing movement of humans, animals, rivers, goods, and food. Territories are constituted by the means of the inflow and outflow of beings and things, which simultaneously transform landscapes and cultures. In this context of displacements, the history of humankind intersects with the narrative of many other lives. This research addresses the crossroads between humans and food in order to understand how their histories are intertwined and permeated by affective relations. Food has great symbolic and material power in human life, performing a bonding role between individuals and their memories, as well as producing a sense of belonging to a given group or place. Seeking to explore these affective dimensions of culinary practices within narratives of displacement, we mean to do a participant observation research with imigrant chefs from an Argentinian restaurant located in Vitória, Espírito Santo, in order do analyse their lives along with the food.